A systematic review: Employee Turnover, Compensation and Benefit to Increase Employee Performance - Parulian, Ronald; Bobby Reza; Imam Suryono; Emmy Junianti (Asian Journal of Applied Business and Management, 2024)
Employee turnover rate still remain of the most frustrating and persistent issues in organization and company over the decades. In Cargo Terminal, Soekarno Hatta International Airport, turnover rate of employees increased in the past few years. The author uses systematic review to research the issue and the goal is to find the relation between compensation and benefit, employee turnover and the impact on the employee performance and also have impact to the company and organization performance. This research uses PRISMA method and PICO to identify the research question and to drive the research from database and search engine such as Science Direct and Google Scholar, and the finding is the compensation and benefit have positive impact and significant effect on employee performance.